Reformulation of Criminal Sanctions for Recidivist Corruption Offenders - Rifqi, Pramidazzura Alifa; Fatma, Mawarni (PT. Anagata Sembagi Education, 2025)
Corruption crimes as extraordinary crimes remain a serious challenge within Indonesia’s criminal justice system, particularly when offenders repeatedly commit corruption after serving their sentences. The phenomenon of corruption recidivism indicates the limited effectiveness of existing criminal sanctions. This study aims to examine the normative vacuum in regulating criminal sanctions for repeat corruption offenders and to formulate directions for reformulating more proportional and effective sanctions. This research employs a normative juridical method using statutory, conceptual, and limited comparative approaches. The findings reveal that Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption Crimes does not explicitly regulate aggravated sanctions for corruption recidivists, while recidivism provisions in Law Number 1 of 2023 on the National Criminal Code remain general in nature. This normative gap results in sentencing inconsistency and weak deterrent effects. The study recommends reformulating criminal sanctions through explicit regulation of corruption recidivism, strengthening additional penalties, and synchronizing the Anti-Corruption Law with the National Criminal Code to enhance the effectiveness of corruption eradication and substantive justice.